Pengenalan Instrumen Investasi Aman bagi Pemula: Strategi Pemberdayaan Masyarakat RW 005 Kelurahan Pondok Aren - Chesia Chaerany; Melisa Ali Bintang Shofiyyah; Nadjendra Faza Zulfia Salsabila; Dien Alhallaj Olvi Novan; Nadhira Eliana Zaki Fadhilla; Solikatus Sa'diyah (LPPI UMN AL WASHLIYAH, 2025)
This community service activity was motivated by the low level of financial literacy among residents at the neighborhood level, which often makes them vulnerable to fraudulent investments. The Eduwira Bhakti KKN Team 13 from UIN Syarif Hidayatullah Jakarta conducted a counseling session on Monday, August 11, 2025, in RW 005 Pondok Aren with the aim of providing basic understanding of safe investment instruments, such as mutual funds and gold, as well as simple strategies for saving and investing. The method used was community education through interactive socialization and open discussion with residents. The event was attended by more than 30 participants from diverse backgrounds. The results showed an increase in community understanding of basic investment concepts and the emergence of critical awareness to avoid illegal investment schemes. Positive responses were demonstrated through residents’ enthusiasm during the Q&A session and recommendations for local government and related institutions to support sustainable financial literacy programs. Thus, this activity contributes to community economic empowerment through improved investment literacy.